2000
DOI: 10.1055/s-2000-6830
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Diplopia

Abstract: The diagnosis of an acquired vertical strabismus is not always straightforward. There is no one specific test that will diagnose a vertical deviation. The clinical presentation, signs, and symptoms are the driving forces that will help lead to the correct diagnosis. Patients with binocular vertical diplopia may have symptoms of recent onset or that have been long-standing. Others may not even be completely aware that their ocular symptoms are attributable to a doubled vertical image. The differential diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…If these posterior ethmoidal branches were the main contributor of arterial supply, ischemic nerve block could be a possible mechanism. [6,7,8] Inflammation may contribute to the trochlear nerve palsy. However, no pain on eye movement and abrupt onset of the palsy did not indicate that it played a causative role in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…If these posterior ethmoidal branches were the main contributor of arterial supply, ischemic nerve block could be a possible mechanism. [6,7,8] Inflammation may contribute to the trochlear nerve palsy. However, no pain on eye movement and abrupt onset of the palsy did not indicate that it played a causative role in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…The complaint of vertical diplopia has a well‐established list of differential diagnoses including decompensated phoria, Myasthenia gravis, thyroid orbital diseases, mechanical interference of the globe or associated muscles, Brown’s syndrome, skew deviation or paralysis of the third or fourth cranial nerves 2 . The cause for the initial presentation was obviously related to the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Common differentials are thyroid ophthalmopathy, blow-out fracture with inferior rectus entrapment, neurological causes like superior oblique palsy, neuromuscular junction abnormalities like myasthenia gravis or, in some cases, cysticercosis of the extraocular muscles. 1 'Silent sinus syndrome' is a rare condition where chronic maxillary sinusitis presents with progressive enophthalmos and hypoglobus in the absence of any symptoms of a sino-inflammatory disease. 2 Kass et al reported 22 cases of the syndrome, of which 5 had ocular signs.…”
Section: Descriptionmentioning
confidence: 99%